2009
DOI: 10.1007/s11517-009-0522-4
|View full text |Cite
|
Sign up to set email alerts
|

Helical axis calculation based on Burmester theory: experimental comparison with traditional techniques for human tibiotalar joint motion

Abstract: In prosthetics and orthotics design, it is sometimes necessary to approximate the multiaxial motion of several human joints to a simple rotation about a single fixed axis. A new technique for the calculation of this axis is proposed, originally based on Burmester's theory. This was compared with traditional approaches based on the mean and finite helical axes. The three techniques were assessed by relevant optimal axis estimation in in vitro measurements of tibiotalar joint motion. A standard jig and radioster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Nevertheless, the incongruency of previous studies regarding analysis of the joint axis and the finding of this study suggest that the ankle joint axis is more complex than expected. 20,22,23,[25][26][27][28][29][30][31][32]48,49,[59][60][61] With the present study, we suggest a new system for PSI of TAR. This process included a learning curve especially regarding planning and construction of guiding block configuration.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, the incongruency of previous studies regarding analysis of the joint axis and the finding of this study suggest that the ankle joint axis is more complex than expected. 20,22,23,[25][26][27][28][29][30][31][32]48,49,[59][60][61] With the present study, we suggest a new system for PSI of TAR. This process included a learning curve especially regarding planning and construction of guiding block configuration.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, the incongruency of previous studies regarding analysis of the joint axis and the finding of this study suggest that the ankle joint axis is more complex than expected. 20 , 22 , 23 , 25 - 32 , 48 , 49 , 59 - 61 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, a reference for the ISAs was obtained geometrically, for example using the condyle-to-condyle line [ 14 , 15 ], the rotation axis of a prosthesis [ 16 ], or anatomical planes [ 17 19 ]. An alternative approach is to adopt a functional procedure to compute the reference axis, as several studies showed that a functional approach outperformed the geometrical one, especially for some ad-hoc applications, such as the design of prostheses [ 12 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The STA may have a strong impact on the calculation of functional quantities, such as the helical axis or instantaneous centre of rotation of a joint, that require the calculation of differential kinematics and strongly rely on accurate marker measurements ( Ancillao, Vochten, Aertbeliën, Decré, & De Schutter, 2019 ; Ehrig, Taylor, Duda, & Heller, 2007 ; Ferraresi, De Benedictis, Franco, Maffiodo, & Leardini, 2017 ; Sancisi, Parenti-Castelli, Corazza, & Leardini, 2009 ). A previous study demonstrated that the Gaussian noise had an impact on the calculation of the helical axis and the effect was larger for the smaller angular displacements of the joint ( Cescon, Cattrysse, & Barbero, 2014 ).…”
Section: Introductionmentioning
confidence: 99%